Political Discourse of Natural Resources and Actor Relations in Environmental Contestation in Mahakam Ulu: Diskursus Politik Sumber Daya Alam dan Relasi Aktor dalam Kontestasi Lingkungan di Mahakam Ulu - Yuliana Lerip; Jauhar B (Universitas Indo Global Mandiri, 2026)
Purpose – This study examines the political discourse of natural resource governance and power relations among actors in environmental management in Mahakam Ulu Regency, East Kalimantan. Methodology – The research employs a qualitative method through literature review and Critical Discourse Analysis (CDA). Data sources include policy documents, civil society reports, academic publications, and relevant media coverage. Findings – The discourse of “development” is used by the state, local elites, and corporations to legitimize extractive expansion such as mining and plantations. This has reduced Indigenous living spaces, reinforced power inequality, and weakened community participation. Alternative discourses on customary land rights have emerged but remain structurally limited. Practical Implications – The study highlights the need for fair and participatory natural resource governance, stronger recognition of Indigenous rights, and sustainable environmental policies. Originality/Value – This research is novel in focusing on Mahakam Ulu as an underexplored borderland region and combining CDA with actor-relational analysis.